La odisea de cristalizar un derecho tributario: el viacrucis de las solicitudes de saldo a favor (2021)
Currently tax related to returns of balances in favor, on the occasion of the measures adopted by part of the National Government and administrative authorities, within the framework of the health emergency derived from COVID-19 that was declared by Decree 417 of March 17, 2020, have issued a series of measures in relation to the return and / or compensation of favorable balances in tax returns in various economic sectors. The previous measures taken by the National Government are to applaud, this allows taxpayers to have a better cash flow in their organizations and more in this economic crisis. However, to the foregoing, it is not valid that to make an automatic return of the balances in favor, and that it is a taxpayer's right to obtain these resources, We had to go to these lengths for it to be implemented.